DAILY DATA VISUALIZATION OF PLANT III PT PETROKIMIA GRESIK VIA DASHBOARD UP DATE - Devita Salsa Gunawan; Erwan Adi Saputra; Faris Harditya Purnama; Sani Sani (Universitas Lambung Mangkurat, 2022)
Dashboard is a visual display, numbers and metrics containing all the data that aims to provide information and help users to make the right and fast decisions based on existing data. From here, the idea of a project Up To Date Dashboard